The MicroRNA miR-181 Is a Critical Cellular Metabolic Rheostat Essential for NKT Cell Ontogenesis and Lymphocyte Development and Homeostasis - Henao-Mejia, Jorge; Williams, Adam; Goff, Loyal A.; Staron, Matthew; Licona-Limón, Paula; Kaech, Susan M.; Nakayama, Maki; Rinn, John L.; Flavell, Richard A. (Immunity (Cambridge, Mass.), 2013)
Regulation of metabolic pathways in the immune system provides a mechanism to actively control cellular function, growth, proliferation, and survival. Here, we report that miR-181 is a nonredundant determinant of cellular metabolism and is essential for supporting the biosynthetic demands of early NKT cell development. As a result, miR-181-deficient mice showed a complete absence of mature NKT cells in the thymus and periphery. Mechanistically, miR-181 modulated expression of the phosphatase PTEN to control PI3K signaling, which was a primary stimulus for anabolic metabolism in immune cells. Thus miR-181-deficient mice also showed severe defects in lymphoid development and T cell homeostasis associated with impaired PI3K signaling. These results uncover miR-181 as essential for NKT cell development and establish this family of miRNAs as central regulators of PI3K signaling and global metabolic fitness during development and homeostasis. •miR-181 regulates cellular metabolic fitness required for robust proliferation•miR-181 is essential for NKT cell development•miR-181 is a PTEN rheostat and a central regulator of the PI3K pathway in vivo•miR-181 is a critical regulator of lymphocyte development and homeostasis